2008
DOI: 10.1007/s12264-008-0910-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation on cognitive functions

Abstract: Sleep deprivation (SD) is a common condition that afflicts many people in modern life. Deficits in daytime performance due to SD are experienced universally. Recent evidence indicates that SD causes impairments in cognitive functions. However, the mechanisms that SD impairs cognitive functions are not clear. This review will focus on the behavioral and neural effects of SD with the aim to elucidate the possible mechanisms of SD-induced deterioration in cognitive functions and to identify directions for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, the indirect excitatory effect of orexin might offset the inhibitory action of adenosine on orexin neurons and consequently reverse the sleeppromoting effect of adenosine. The modulation of orexin neurons plays an important role in regulating sleep and wakefulness, especially under prolonged wakefulness in which sleep pressure is enhanced rapidly due to the large release of endogenous adenosine [35] . Caffeine, a nonselective adenosine receptor antagonist, is a widely used stimulant that effectively reverses the depressant effects of increasing sleep propensity [36] , although the sideeffect of drug-dependence has restricted its therapeutic use as an arousal-promoting agent [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the indirect excitatory effect of orexin might offset the inhibitory action of adenosine on orexin neurons and consequently reverse the sleeppromoting effect of adenosine. The modulation of orexin neurons plays an important role in regulating sleep and wakefulness, especially under prolonged wakefulness in which sleep pressure is enhanced rapidly due to the large release of endogenous adenosine [35] . Caffeine, a nonselective adenosine receptor antagonist, is a widely used stimulant that effectively reverses the depressant effects of increasing sleep propensity [36] , although the sideeffect of drug-dependence has restricted its therapeutic use as an arousal-promoting agent [37] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to consider the effect that sleep loss has on cognitive performance and mood. It is well established that sleep loss degrades cognitive performance [57]. Previous studies in military populations have consistently shown impairments in vigilance, reaction time and working memory [58,59].…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Sleep plays a key role in human life and work, but sleep deprivation (SD), namely irregular and inadequate sleep, shows a rising trend in today’s society (Feng et al, 2016; Honn et al, 2018). Therefore, the association between SD and cognitive impairment has been paid close attention (Zhang and Liu, 2008; Jin et al, 2017; Li S. et al, 2017). It is well known that SD affects human health and work efficiency (Honn et al, 2018) and that SD is a common state leading to a global cognitive decline for individuals (Jackson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%